# Solve for z 6/5*(5z-1)-4z=7/5

65⋅(5z-1)-4z=75
Simplify 65⋅(5z-1)-4z.
Simplify each term.
Apply the distributive property.
65(5z)+65⋅-1-4z=75
Cancel the common factor of 5.
Factor 5 out of 5z.
65(5(z))+65⋅-1-4z=75
Cancel the common factor.
65(5z)+65⋅-1-4z=75
Rewrite the expression.
6z+65⋅-1-4z=75
6z+65⋅-1-4z=75
Multiply 65⋅-1.
Combine 65 and -1.
6z+6⋅-15-4z=75
Multiply 6 by -1.
6z+-65-4z=75
6z+-65-4z=75
Move the negative in front of the fraction.
6z-65-4z=75
6z-65-4z=75
Subtract 4z from 6z.
2z-65=75
2z-65=75
Move all terms not containing z to the right side of the equation.
Add 65 to both sides of the equation.
2z=75+65
Combine the numerators over the common denominator.
2z=7+65
2z=135
2z=135
Divide each term by 2 and simplify.
Divide each term in 2z=135 by 2.
2z2=135⋅12
Cancel the common factor of 2.
Cancel the common factor.
2z2=135⋅12
Divide z by 1.
z=135⋅12
z=135⋅12
Multiply 135⋅12.
Multiply 135 and 12.
z=135⋅2
Multiply 5 by 2.
z=1310
z=1310
z=1310
The result can be shown in multiple forms.
Exact Form:
z=1310
Decimal Form:
z=1.3
Mixed Number Form:
z=1310
Solve for z 6/5*(5z-1)-4z=7/5

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top